Effects of potassium fertilizer reduction combined with polyaspartic acid application on yield, quality, processing characteristics, rhizosphere microbial composition and metabolites of flue-cured tobacco - Zhang, Haoran; Tian, Hui; Zhang, Zetao; Chai, Guohua; Wu, Xiuwen (Frontiers in Plant Science, 2025)
IntroductionThe extensive application of potassium (K) in tobacco has exacerbated the shortage of K mineral resources in China. Polyaspartic acid (PASP) had shown significant effects in promoting the absorption of K, increasing the utilization rate of K fertilizer, and improving yield and quality of tobacco.MethodsTo clarify the potential and mechanism of PASP replacing some K fertilizers in tobacco production, field experiment was conducted with 4 different treatments: NK (traditional fertilization); RT (10% reduction of K fertilizer); NKP (traditional fertilization +4% PASP/total K2O); RKP (10% reduction of K fertilizer +4% PASP/total K2O).ResultsThe reduction of K inhibited leaf growth, yield formation, K absorption, improved stem rate and decreased thickness, tensile strength, elongation rate and leaf surface density of flue-cured leaves, while had no effect on N, P, Cl content and rate of total sugar and nicotine. Comparing to NK, NKP raised the total yield by 16.7%, promoted physical properties and chemical quality optimization of flue-cured leaves. What is more, RKP compensated for the decrease in leaf yield, K content, processing utilization rate and sugar/nicotine of different parts caused by K reduction. However, K reduction and PASP application obviously influenced metabolite composition of rhizosphere soil without affecting the microbial community composition, and our results showed a relatively high correlation between differential metabolites and yield, K content, sugar/nicotine ratio, elongation rate of flue-cured tobacco.ConclusionOverall, PASP provided better optimization effects on tobacco growth, yield, physical properties, chemical quality of flue-cured leaves, and PASP was beneficial for replacing K fertilizer to a certain extent, reducing the consumption of K mineral resources and environmental pollution.